Age and gender differential relationship between employment status and body mass index among middle-aged and elderly adults: a cross-sectional study. Issue 11 (15th November 2016) - Noh, Jin-Won; Kim, Jinseok; Park, Jumin; Oh, In-Hwan; Kwon, Young Dae
Abstract : Objective: To determine the influence of age and gender, respectively, on the association between employment status and body mass index (BMI) in Korean adults using a large, nationally representative sample. Design: Cross-sectional study. Setting: South Korea. Participants: 7228 from fourth wave of the Korean Longitudinal Study of Aging (KLoSA), the survey's short form and year: 'KLoSA 2012'. Main outcome measures: BMI. Results: BMI among the employed was higher than among the unemployed for those under 60. In terms of gender, employed men reported higher BMI than their unemployed counterparts, whereas employed women reported lower BMI than did unemployed women. Conclusions: Employment status showed varying impacts on obesity by age and gender. Both unemployment at or after 60, as well as unemployment among women, is associated with increased BMI compared with unemployment among younger individuals or men, respectively.